Сlinical and economic evaluation of various etiotropic chemotherapy regimens in patients with respiratory tuberculosis with multidrug and extensively drug resistance - N. Yu. Nikolenko; D. A. Kudlay; S. E. Borisov; T. E. Sannikova; N. P. Doktorova (Фармакоэкономика, 2023)
Objective: analysis of clinical and economic efficiency of various etiotropic chemotherapy regimes in patients with respiratory tuberculosis with multidrug- and extensively drug-resistant (MDR and XDR) pathogen using the pharmacoeconomic modeling method (Markov model).Material and methods. A single-centre, observational, retrospective, cohort study was performed, which included patients who received treatment in clinics and affiliated organizations of the main Moscow tuberculosis institution during 2014–2019 regarding respiratory tuberculosis with the MDR/XDR pathogen. The data of 1387 patients were analysed, of which 1093 patients received “optimized basic regimen” (OBR) in accordance with the Federal Clinical Recommendations of 2015, 294 patients received etiotropic therapy in accordance with the recommendations of the World Health Organization of 2018–2019. To evaluate economic efficiency, the pharmacoeconomic costeffectiveness analysis and pharmacoeconomic modeling were used. When assessing the economic costs of treatment, the direct costs (medical and non-medical) were taken into account.Results. The study results showed that 68.4% of patients in the group with bedaquiline-containing chemotherapy regimens reached the outcome of “treatment successfully completed” (patient was cured or transfered into the III group of dispensary follow-up) compared to 51.8% in the OBR group. The use of “new” etiotropic therapy regimens is most economically justified in patients with ХDR-tuberculosis with repeated treatment courses: incremental cost-effectiveness ratios (ICER) were 24,530.20 and 21,526.50 rubles per 1 patient. Markov model was developed, transitions from one state to another were evaluated according to the results of clinical observations during the first 2 years of research.Conclusion. The use of the dynamic model of the patient state made it possible to refine the estimates of the effectiveness of the compared etiotropic chemotherapy regimens for tuberculosis with MDR/XDR pathogen. Based on the results of modeling the dynamics of patients in the interval of 2 to 10 years of treatment, the use of “new” regimens provides a significant increase in the proportion of treatment success (by 16.1–29.8% in different groups of patients and at different times), a decrease in mortality (by 6.1–11.0%), and in the proportion of those who interrupted treatment (by 8.0–21.8%) in comparison with OBR.